Insults in Classical Athens - Kamen, Deborah (Wisconsin Studies in Classics Ser, 2020)
Intro -- Contents -- Acknowledgments -- Conventions and Abbreviations -- Introduction -- 1. Skōmmata and Aischrologia: Benign Insults -- 2. Kōmōidein and Skōptein: Mockery in Old Comedy -- 3. Diabolē and Loidoria: Invective in Attic Oratory -- 4. Kakēgoria and Aporrhēta: Forbidden Verbal Abuse -- 5. Hubris: Affronts to Honor -- Conclusion -- Notes -- References -- Index -- Index Locorum.